Performing kayepa dordok living waters in Noongar boodjar, South‐Western Australia. (28th September 2021) - Bracknell, Clint; Horwitz, Pierre; Ryan, Trevor; Marshall, Jonathan W.
Abstract: Performance through language, song and dance provides alternative knowledges and ways of understanding, in this case, developing deeper relationships with living water. Drawing on Indigenous Noongar culture from south‐western Australia, this paper addresses the question: How can relationships between living underground, estuarine and riverine water bodies ( kayepa dordok ) be performed? Two new interlinked Noongar works in response to local riverscapes were developed for, and performed as part of, the 2021 Perth Festival. The first was to embody the return journey of the bullshark, from the salt water to the riverine fresh water; the second was to enact the presence of the unseen groundwater – which emerges as wetlands and estuaries strewn throughout the landscape – on its return to the sea. The method used to derive the song and dance, and the impact of the performance itself, are described. The experiment makes a case for multiple benefits associated with re‐establishing connections among culture and nature by drawing on Indigenous perspectives, through performance giving voice to a relationality between river systems and people.